2022
DOI: 10.1021/acs.biochem.2c00367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Corrinoid Profiles across Host-Associated and Environmental Samples

Abstract: Vitamin B 12 (the cyanated form of cobalamin cofactors) is best known for its essential role in human health. In addition to its function in human metabolism, cobalamin also plays important roles in microbial metabolism and can impact microbial community function. Cobalamin is a member of the structurally diverse family of cofactors known as cobamides that are produced exclusively by certain prokaryotes. Cobamides are considered shared nutrients in microbial communities because the majority of bacteria that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
5
14
1
Order By: Relevance
“…5), though current methods do not allow us to separate cell-associated from extracellular corrinoids. Combined with our previous LC-MS results that showed approximately 95% of the corrinoid in soil collected from the same site is cobalamin [53], we estimate that the soil contained approximately 39 pmol cobalamin and 2 pmol 5-methylbenzimidazolylcobamide per gram. Based on an estimate of 10 9 microbial cells per gram of soil, this soil contains approximately 10 4 corrinoid molecules per microbial cell, a level sufficient to support maximal growth of bacteria in pure culture, and far above that required by corrinoid-dependent isolates obtained from this soil [14, 18, 54, 55].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…5), though current methods do not allow us to separate cell-associated from extracellular corrinoids. Combined with our previous LC-MS results that showed approximately 95% of the corrinoid in soil collected from the same site is cobalamin [53], we estimate that the soil contained approximately 39 pmol cobalamin and 2 pmol 5-methylbenzimidazolylcobamide per gram. Based on an estimate of 10 9 microbial cells per gram of soil, this soil contains approximately 10 4 corrinoid molecules per microbial cell, a level sufficient to support maximal growth of bacteria in pure culture, and far above that required by corrinoid-dependent isolates obtained from this soil [14, 18, 54, 55].…”
Section: Resultssupporting
confidence: 69%
“…These results could mean that much of the cobalamin detected in soil is bioavailable, and that cobalamin is not a limiting micronutrient in this environment. In nature, the introduction of corrinoids other than cobalamin to soil may mimic the interplay between soil fauna and microbes; the gut and fecal contents of several invertebrates and macrofauna have been found to contain diverse corrinoids that microbes may transiently encounter [53]. Indeed, we have observed that corrinoid-dependent taxa isolated from this soil are able to use many corrinoids undetected in this soil, with different affinities for each [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of excess corrinoid in our isolation media, we recovered fewer corrinoid-dependent isolates than expected (26,57), which may be due to corrinoid-dependent bacteria having additional nutrient dependencies not satisfied by our isolation medium or requiring specific partners for their survival (6). Notably, all of the dependent isolates were able to use corrinoids that have not been detected in this soil (30).…”
Section: Discussionmentioning
confidence: 99%
“…1A), which has been shown to impact function – microbial preferences for particular corrinoid structures are apparent in their differential growth responses to corrinoids (17,29). Distinct groups of corrinoids have been detected in a variety of host-associated and environmental microbial communities, suggesting that microbes encounter diverse corrinoids in nature (30). Because most corrinoids are not commercially available, nearly all research on corrinoids has been performed only with B 12 (17).…”
Section: Introductionmentioning
confidence: 99%
“…strain 5OH_020 was isolated from ungrazed grassland topsoil at the Hopland Research and Extension Center (39.00 N 123.08 W) by limiting dilution in methionine-dropout VL60 medium containing 0.1 g/L each of xylan, glucose, xylose, and N-acetyl glucosamine (1), amended with 10 nM 5-hydroxybenzimidazolyl cobamide ([5-OHBza]Cba) that we synthesized according to (2). [5-OHBza]Cba is a commercially-unavailable cobamide cofactor typically biosynthesized by methanogens and found in diverse environments such as animal gastrointestinal tracts and contaminated groundwater (3, 4, 5). To our knowledge, this is the first report of a bacterium isolated on a cobamide other than vitamin B 12 (cobalamin).…”
Section: Announcementmentioning
confidence: 99%